Open compositionality towards a new methodology of language - García Ramírez, Eduardo (Lexington Books, 2019)
Open Compositionality: Towards a Methodology of Language offers a fresh view into human languages as supermodular, highly interactive cognitive capacities allowing for human unique thought and communication. It is a novel account of semantics as decision-making in tandem with the cognition first methodology.